1987
DOI: 10.1056/nejm198706113162401
|View full text |Cite
|
Sign up to set email alerts
|

High-Dose Therapy and Autologous Bone Marrow Transplantation after Failure of Conventional Chemotherapy in Adults with Intermediate-Grade or High-Grade Non-Hodgkin's Lymphoma

Abstract: Adult patients with advanced non-Hodgkin's lymphoma in whom conventional chemotherapy has failed are seldom cured thereafter. We studied 100 such patients with intermediate-grade or high-grade non-Hodgkin's lymphoma who were subsequently treated with high-dose chemotherapy (61 patients) or high-dose chemotherapy plus total-body irradiation (39 patients), with bone marrow transplantation used for hematologic support. Thirty-four patients had disease that had been refractory to primary chemotherapy, and 66 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
274
1
6

Year Published

1989
1989
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 750 publications
(292 citation statements)
references
References 27 publications
11
274
1
6
Order By: Relevance
“…Of particular importance, these responses are seen in a heavily pretreated population with several poor prognostic features such as chemo-resistant disease (Josting et al, 2000), relapse within a year (Brice et al, 1997;Guglielmi et al, 1998), advanced disease stage (Blay et al, 1998) and previous ASCT. Response to salvage chemotherapy is important prior to ASCT, as it is correlated with survival post-transplant (Philip et al, 1987;Brice et al, 1997). Another significant finding was that treatment with GEM-P did not appear to inhibit stem cell harvesting, although this was not an end point of the study.…”
Section: Discussionmentioning
confidence: 99%
“…Of particular importance, these responses are seen in a heavily pretreated population with several poor prognostic features such as chemo-resistant disease (Josting et al, 2000), relapse within a year (Brice et al, 1997;Guglielmi et al, 1998), advanced disease stage (Blay et al, 1998) and previous ASCT. Response to salvage chemotherapy is important prior to ASCT, as it is correlated with survival post-transplant (Philip et al, 1987;Brice et al, 1997). Another significant finding was that treatment with GEM-P did not appear to inhibit stem cell harvesting, although this was not an end point of the study.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4] Patients in chemotherapy-sensitive relapse have improved survival with autologous SCT. 5,6 Several studies have been published in an attempt to discern the optimal conditioning regimen before stem cell infusion. These have included BCNU or TBI combined with etoposide and CY, TBI with etoposide and CY, carmustine, cytarabine, CY and etoposide (BEAC), or BCNU, etoposide, ara-c and melphalan (BEAM).…”
Section: Discussionmentioning
confidence: 99%
“…4 High-dose chemotherapy followed by autologous SCT has been shown to be potentially curative for patients who relapse after initial chemotherapy. 5 SCT in second or third CR was established as a standard of care by the Parma trial in patients between 18 and 60 years of age with intermediate or high-grade NHL. The study reported an event-free survival of 46% at 5 years in the transplantation group as compared with 12% in the group receiving chemotherapy without transplant.…”
Section: Introductionmentioning
confidence: 99%
“…Two patients had reversible impairment of renal function and cisplatin was omitted in one and two courses respectively. The dose of etoposide was reduced by 25% in two patients (Philip et al, 1987). Moreover, long term disease free survival is around 20% in non selected groups of patient, (Takvorian et al, 1987;Appelbaum et al, 1987;Phillips et al, 1990) results not much better than those achieved with conventional salvage therapy alone.…”
Section: Patient Selectionmentioning
confidence: 92%